Systematic comparison of a new generation of columns packed with sub‐2 μm superficially porous particles. Issue 3 (6th January 2014) - Bobály, Balázs; Guillarme, Davy; Fekete, Szabolcs
Abstract : The aim of this study was to evaluate the possibilities/limitations of recent RP‐LC columns packed with 1.6 μm superficially porous particles (Waters Cortecs) and to compare its potential to other existing sub‐2 μm core–shell packings. The kinetic performance of Kinetex 1.3 μm, Kinetex 1.7 μm and Cortecs 1.6 μm stationary phases was assessed. It was found that the Kinetex 1.3 μm phase outperforms its counterparts for ultra‐fast separations. Conversely, the Cortecs 1.6 μm packing seemed to be the best stationary phase for assays with longer analysis time in isocratic and gradient modes, considering small molecules and peptides as test probes. This exceptional behaviour was attributed to its favourable permeability and somewhat higher mechanical stability (Δ P max of 1200 bar). The loading capacity of these three columns was also investigated with basic and neutral drugs analysed under acidic conditions. It appears that the loading capacities of Cortecs 1.6 μm and Kinetex 1.7 μm were very close, while it was reduced by 2–7‐fold on the Kinetex 1.3 μm packing. However, this observation is dependent on the nature of the compound and certainly also on mobile phase conditions.